Penggunaan Media Puzzle untuk Meningkatkan Hasil Belajar Peserta Didik pada Pembelajaran IPA - Angela Herlina Londa; Yuliana Yenita Mete; Berty Sadipun (Journal of Elementary School (JOES), 2018)
The research aims at improving students science achievement at the fourth grade of SDI Bhoanawa 1 South Ende subdistrict, Ende regency. The research design was classroom action research (CAR) with Kemmis Mc Taggart model. The subject of the research was 16 students of class IV B. The techniques to collect the data were observation, documentation, and test. The result showed the improvement of the score for science subject with material " the benefit of living things" which was proved by the treatments in cycle I and cycle II. The achievement percentages were 37,5%, 62,5%, dan 100% with average 90, 31. In conclusion, the application of puzzles improved students science learning Keywords: Achievement, Puzzles, Science Learning